Optimization of energy and directional response of a small 4π silicon dosemeter for quality control of CT/CBCT-units – A 3D CAD, Monte-Carlo, AM approach. (April 2020) - Herrnsdorf, L.; Andersson, M.; Gunnarsson, M.; Mattsson, S.
Abstract: A 4π radiation dosemeter for use in medical radiology was designed. It is based on a solid state silicon detector, a sensor wafer, a flex card, a 3D plastic holder and a spherical stainless steel filter with a distribution of holes around the detector. The detector is attached to the wafer using only low Z material. To achieve an energy and directional response which is as uniform as possible for various radiation qualities and beam directions, the filter was designed using a series of Monte Carlo calculations. The energy filter and its hole pattern were created using Additive Manufacturing (AM) in the form of metal 3D printing. The functionality of the dosemeter was designed to fulfill the quality criteria of a combined energy and angular dependence of less than 5% for the IEC beam qualities RQR and RQT in the range of 65–145 kV. This is a major improvement to the existing solutions that may need software corrections to be used for the same beam quality range. Highlights: Development of a pure silicon detector specialised for diagnostic radiology (CT, CBCT, and planar radiography) examinations. Creating an energy and angular independent 4π filter for3D dose measurement based on Monte Carlo simulations. Enable measurements with high spatial and temporal resolution for 3D dose profiles arbitrary geometries.